The diagnostic contribution of motor and sensory conduction studies of the wrist-palm segment in carpal tunnel syndrome - Tuğan Yıldız, Buket; Şener, Özden (Journal of Surgery and Medicine, 2019)
Aim: Sensory and motor segmental conduction studies have been performed to improve diagnostic sensitivity especially in cases with mild carpal tunnel syndrome, but there are very few studies comparing these methods. The purpose of this study was to determine the segmental conduction studies' contribution to the diagnosis of carpal tunnel syndrome (CTS), to compare the sensitivity and specificity of these methods. Methods: Patients with suspected CTS referred to our electrophysiology laboratory and a control group was included. The data were collected prospectively. The following measurements made: median sensory conduction velocity wrist- digit 1 (W-1), median sensory conduction velocity wrist- digit 3 (W-3), median wrist-palm sensory conduction velocity (W-Ps), distoproximal ratio of velocity (D/P), median distal motor latency wrist- APB (MDML), median wrist- palm segment motor conduction velocity (W-Pm). Results: The highest sensitivity for an electrodiagnostic CTS diagnosis were W- Pm (38%), D/P (33.3%), MDML (33.3%), W- 3 (31%), W- 1 (31%), W-Ps (24%), respectively. Seventeen out of 42 hands presented one or more abnormal results of routine electrophysiologic tests (W-1, W-3, MDML). Twenty-one patients were diagnosed CTS electrophysiologically after inclusion of D/ P and 24 patients were defined CTS after inclusion of W- Pm. Twenty-five of 42 hands with CTS were defined as an electrophysiologically proven CTS using routine electrophysiologic tests together with both D/P and W-Pm segmental studies. That is; diagnostic sensitivity increased nearly by 50%. Conclusion: The results of this study suggested that motor or sensory segmental studies have an important contribution to the diagnosis, particularly for mild subjects.